Uncovering trends in destination branding and destination brand equity research: Results of a topic modelling approach - János Csapó; Sita Dewi Kusumaningrum (Journal of Tourism, Heritage & Services Marketing)
Purpose: This study aims to explore the trends and topics in destination branding research, with a specific focus on destination brand equity (DBE). Using topic modelling analysis, the study identifies key research themes and evaluates their evolution over time, assessing whether DBE is among the trending topics.